CLINICAL AND NEUROLOGICAL FEATURES OF POLYNEUROPATHY OF CORONAVIRUS AND DIABETIC ETIOLOGY (International journal of medical sciences, 2026)
Relevance. Polyneuropathies of various etiologies represent one of the pressing problems of modern clinical neurology. In the post-COVID period, lesions of the peripheral nervous system are being increasingly reported, the clinical manifestations of which require differential diagnosis with diabetic polyneuropathy.Objective. To perform a comparative assessment of the clinical and neurological manifestations of polyneuropathy of coronavirus and diabetic etiology.Materials and Methods. A total of 95 patients with polyneuropathy were examined: 57 with coronavirus-associated polyneuropathy and 38 with diabetic polyneuropathy. The control group consisted of 30 practically healthy individuals. Assessment included clinical and neurological examination, the Total Symptoms Score, the Visual Analogue Scale for pain, and the Spielberger–Hanin Anxiety Scale.Results. Patients with coronavirus-associated polyneuropathy demonstrated a higher intensity of pain syndrome and more pronounced anxiety-affective disorders. Sensory disturbances showed comparable prevalence in both groups but differed in structure and stability. Motor impairments were more pronounced in patients with diabetic polyneuropathy.Conclusions. Polyneuropathies of coronavirus and diabetic etiology have similar clinical manifestations; however, they differ in pain severity, the characteristics of sensory and motor disturbances, and the influence of psycho-emotional factors. These differences should be taken into account in diagnosis and in the selection of treatment and rehabilitation strategies.